Peningkatan Hasil Belajar Siswa dalam Pembelajaran Pkn Ddengan Model Problem Based Learning (PBL) - Gusriyenti, Melly Putri; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to explain the improvement of student learning outcomes in Civic learning using the Problem Based Learning (PBL) model in class V SD Koto Gunung, Pesisir Selatan. The type of this research is Classroom Action Research (CAR) using a qualitative and quantitative approach. The study subjects were teachers and 16  students in the grade. This study was conducted in two cycles. Research procedures include, (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the study showed an increase in RPP in the first cycle with an average value of 83.91% (B) and the second cycle with an average value of 92.87% (B). Aspects of teachers of the first cycle with an average value of 78.57% (B) and the second cycle with an average value of 91.06% (SB). Aspects of first cycle students with an average value of 74.99% (C) and the second cycle with an average value of 91.06% (SB). Student learning outcomes of cycle I with an average value of 73.35 (C) and cycle II with an average value of 84.27 (SB). Therefore, the Problem-Based Learning (PBL) model can improve student learning outcomes in Civics in Primary Schools.